Prevalence of Sarcocystis sp. in cattle, sheep and goats in abattoirs of Lima - Castro, Julia (1992)
A study about the prevalence of Sarcocystis sp. in bovine, ovine and goat cattle have been performed using the Trichinoscopy method into heart and esophagus tissues. The results showed that 76 samples of heart tissues from bovine positive over a total of 85 samples (89.5%); will 122 samples from ovine were positive over a total of 134 samples (91.04%). In the same tissue of goat only 33 samples (52.4%). Sarcocystis was found in esophagus the parasitism average was as follow: 2% in bovine; 39.8 in ovine and 76.2 in goat. These results achieved that the mayor parasitism in bovine and ovine is located into the heart; whilst in goat the esophagus is the tissue more infect. Therefore a high parasitism by Sarcocystis sp. has been registered in the meat of cattle used as a human food.